KOALISI PARTAI ISLAM DAN WACANA PEMBELAHAN SOSIAL DALAM SISTEM PEMILIHAN PRESIDEN INDONESIA - Azmi, Mohammad Fazrulzaman (Bawaslu Provinsi Jawa Barat, 2023)
This study explains the causal relationship between the presidential election system, social cleavages and religious identity, and the pattern of Islamic parties in forming coalitions in presidential elections. Why is Islamic identity no longer the main channel? How does the electoral system affect this problem? In the process, this research uses a qualitative approach by applying the tracing method to explain the research phenomenon. The research found that Indonesia’s presidential election system tends to be categorized as a majoritarian system with an emphasis on gaining more than 50% of the vote. Consequently, social cleavages are narrowing so that political parties tend to be center-oriented or pragmatic. This can be proven by the dynamics of coalition patterns formed in Islamic parties. They do not form a unity to emphasize Islamic identity or social cleavage as a major power, but they try to combine nationalist and religious elements in nominating candidates.